정부연구비 지원 변동이 기초연구성과에 미치는 영향 분석: IT 분야를 중심으로 - 연승민; 김슬기; 김재수; 이병희; Yeon, Seungmin; Kim, Seulki; Kim, Jae-Soo; Lee, Byeong-Hee (한국콘텐츠학회 논문지, 16(5), 2016)
The aim of this study is to analyze the relationship between fluctuations of a government subsidy and research outputs on the basic research field. An analysis of this study was conducted on basic research projects specifically on the field of information technology (IT) filed at university and Individual Research Programs of Korean ministry. Using various project characteristic variables, relationship between dependent variables and independent variables was controlled. To summarize results of a regression analysis, from looking at the correlation between fluctuations of a government subsidy and basic research outputs (weighted papers and patents), the result showed a positive relationship. The maximum effect of increased research funding projects on research outputs was 8 times greater than an effect of maintained funding projects. Moreover, the maximum effect of decreased research funding projects on research outputs was 4 times greater than an effect of maintained funding projects. Base on this result, we suggested implications from academic and practical aspects. 본 연구의 목적은 기초연구분야에서 정부연구비의 변동과 연구성과간의 관계를 파악하는데 있다. 이를 위해, 개인연구사업 중 대학에서 수행된 IT 분야의 기초연구과제들을 대상으로 분석을 실시하였다. 여러 과제 특성 변수를 활용하여, 종속변수와 독립변수와의 관계를 통제하였다. 회귀분석결과를 살펴보면, 정부 연구비 증감은 모든 연구성과(가중논문 수, 특허 수)와 통계적으로 유의미한 정(+)의 관계에 있는 것으로 분석되었다. 또한, 연구성과에 가장 큰 영향을 미치는 과제는 연구비가 증액된 과제로, 연구비가 유지된 과제에 비해 최대 8배 정도의 큰 영향력을 보였다. 연구비가 감액된 과제는 연구비가 유지된 과제에 비해 최대 4배 정도의 큰 영향력을 갖은 것으로 확인하였다. 이러한 연구결과를 기반으로 학술적 측면, 실무적 측면의 시사점을 제시하였다.